PERANCANGAN APLIKASI MOBILE LEARNING PADA MATA PELAJARAN BIOLOGI KELAS X DI SMAN 1 RAO UTARA - Elfia, Nur Elfia; Zakir, Supratman; i, Supriadi; Efriyanti, Liza (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
This examine objectives to create a generation-based totally learning medium inside the form of a cellular studying software for Biology subjects in Grade X at SMAN 1 Rao Utara. A common trouble faced in Biology getting to know is the confined availability of interactive educational media that students can get right of entry to whenever and anywhere. The studies technique employed is studies and development (R&D) using the ADDIE development model, which includes 5 degrees: evaluation, design, improvement, Implementation, and assessment. The utility became advanced using web programming languages and capabilities essential additives together with studying materials, instructional films, and assessment quizzes. The results from the testing section imply that the advanced mobile getting to know software received fine comments from concern matter experts, media experts, and students as end users. consequently, this application is expected to contribute to improving students' motivation and information of Biology subjects.